A Phase III Study of Pafolacianine Injection (OTL38) for Intraoperative Imaging of Folate Receptor–Positive Ovarian Cancer (Study 006). Issue 2 (7th September 2022) - Tanyi, Janos L.; Randall, Leslie M.; Chambers, Setsuko K.; Butler, Kristina A.; Winer, Ira S.; Langstraat, Carrie L.; Han, Ernest S.; Vahrmeijer, Alexander L.; Chon, Hye Sook; Morgan, Mark A.; Powell, Matthew A.; Tseng, Jill H.; et al.
Abstract : PURPOSE: The adjunctive use of intraoperative molecular imaging (IMI) is gaining acceptance as a potential means to improve outcomes for surgical resection of targetable tumors. This confirmatory study examined the use of pafolacianine for real-time detection of folate receptor–positive ovarian cancer. METHODS: This phase III, open-label, 11-center study included subjects with known or suspected ovarian cancer, scheduled to undergo cytoreductive surgery. The objectives were to confirm safety and efficacy of pafolacianine (0.025 mg/kg IV), given ≥ 1 hour before intraoperative near-infrared imaging to detect macroscopic lesions not detected by palpation and normal white light. RESULTS: From March 2018 through April 2020, 150 patients received a single infusion of pafolacianine (safety analysis set); 109 patients with folate receptor–positive ovarian cancer comprised the full analysis set for efficacy. In 33.0% of patients (95% CI, 24.3 to 42.7; P < .001), pafolacianine with near-infrared imaging identified additional cancer on tissue not planned for resection and not detected by white light assessment and palpation, exceeding the prespecified threshold of 10%. Among patients who underwent interval debulking surgery, the rate was 39.7% (95% CI, 27.0 to 53.4; P < .001). The sensitivity to detect ovarian cancer was 83%, and the patient false-positive rate was 24.8%. Investigators reported achieving complete R0 resection in 62.4% (68 of 109) of patients. Drug-related adverse events were reported by 30% of patients (45 of 150) and most commonly included nausea, vomiting, and abdominal pain. No drug-related serious adverse events or deaths were reported. CONCLUSION: This phase III study of pafolacianine met its primary efficacy end point, identifying additional cancers not otherwise identified or planned for resection. Pafolacianine may offer an important real-time adjunct to current surgical approaches for ovarian cancer.